Prediction of cervical cancer recurrence using textural features extracted from (18)F-FDG PET images acquired with different scanners - Reuzé, Sylvain (Oncotarget, 2017)
OBJECTIVES: To identify an imaging signature predicting local recurrence for locally advanced cervical cancer (LACC) treated by chemoradiation and brachytherapy from baseline (18)F-FDG PET images, and to evaluate the possibility of gathering images from two different PET scanners in a radiomic study. METHODS: 118 patients were included retrospectively. Two groups (G1, G2) were defined according to the PET scanner used for image acquisition. Eleven radiomic features were extracted from delineated cervical tumors to evaluate: (i) the predictive value of features for local recurrence of LACC, (ii) their reproducibility as a function of the scanner within a hepatic reference volume, (iii) the impact of voxel size on feature values. RESULTS: Eight features were statistically significant predictors of local recurrence in G1 (p < 0.05). The multivariate signature trained in G2 was validated in G1 (AUC=0.76, p<0.001) and identified local recurrence more accurately than SUV(max) (p=0.022). Four features were significantly different between G1 and G2 in the liver. Spatial resampling was not sufficient to explain the stratification effect. CONCLUSION: This study showed that radiomic features could predict local recurrence of LACC better than SUV(max). Further investigation is needed before applying a model designed using data from one PET scanner to another.